The Expectation-Reality Gap: An Analysis Of The Mathematics Education Program’s Relevance At Iain Curup Based On Senior High School Teachers And Students Feedback - Irni Latifa Irsal; Anisya Septiana; Tasha Marshanda; Ivo Novinda (Educate : Journal of Education and Learning, 2025)
This study aims to examine the perceptions of teachers and students regarding the existence of the Mathematics Education Study Program at IAIN Curup. A mixed-methods approach with a concurrent triangulation strategy was employed. A total of 47 teachers completed an open questionnaire, while 536 students responded to a closed  questionnaire. Quantitative data were analyzed using descriptive statistics, and qualitative data were analyzed through thematic analysis. The results reveal two contrasting perspectives. From the teachers' perspective, the Mathematics Education Study Program at IAIN Curup is perceived positively, with 65.96% of teachers considering it worthy of recommendation to their students. Teachers identified the program's proximity to schools as its primary advantage. Conversely, from the students' perspective, the program's existence is perceived poorly, with 81.72% of students unaware of the program and 95.52% expressing no interest in enrolling. The study concludes that there is a significant gap between teachers' and students' perceptions, which may contribute to the declining student enrollment. Recommendations include strengthening promotional strategies and enhancing program visibility through community engagement.